2018
DOI: 10.1038/s41421-018-0026-1
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM structure of the ASIC1a–mambalgin-1 complex reveals that the peptide toxin mambalgin-1 inhibits acid-sensing ion channels through an unusual allosteric effect

Abstract: Acid-sensing ion channels (ASICs) are neuronal voltage-independent Na+ channels that are activated by extracellular acidification. ASICs play essential roles in a wide range of physiological processes, including sodium homeostasis, synaptic plasticity, neurodegeneration, and sensory transduction. Mambalgins, a family of three-finger toxins isolated from black mamba venom, specifically inhibit ASICs to exert strong analgesic effects in vivo, thus are thought to have potential therapeutic values against pain. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 55 publications
3
49
0
1
Order By: Relevance
“…; Sun et al . ). The swallowing threshold induced by a series of von Frey filaments was measured before and after topical administration of 3 μl aliquots of amiloride (0.3–30 nmol), benzamil (0.3–30 nmol), dimethylamiloride (0.3–30 nmol), DMSO (1%–100%), gadolinium (0.3–30 nmol), mambalgin‐1 (0.3–30 nmol) and diminazene (0.3–30 nmol).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…; Sun et al . ). The swallowing threshold induced by a series of von Frey filaments was measured before and after topical administration of 3 μl aliquots of amiloride (0.3–30 nmol), benzamil (0.3–30 nmol), dimethylamiloride (0.3–30 nmol), DMSO (1%–100%), gadolinium (0.3–30 nmol), mambalgin‐1 (0.3–30 nmol) and diminazene (0.3–30 nmol).…”
Section: Methodsmentioning
confidence: 97%
“…We used the ENaC blocker amiloride, its analogues benzamil and dimethylamiloride, the vehicle of amiloride analogues dimethyl sulfoxide (DMSO), the classic mechanosensitive channel blocker gadolinium, and the ASIC inhibitors mambalgine-1 and diminazene. Mambalgine-1 is an ASIC-1a and -1b inhibitor, and diminazene is an ASIC-1a, -1b, -2a and -3 inhibitor (Chen et al 2010;Diochot et al 2012;Sun et al 2018). The swallowing threshold induced by a series of von Frey filaments was measured before…”
Section: Effect Of Nerve Transection and Topical Drug Application On mentioning
confidence: 99%
“…Mourier et al performed full concentration-response curves, and showed >10fold loss in IC50 for mutants F27A, R28A, L32A, I33A, and L34A, concluding that these residues are crucial for the ASIC1a interaction. A second study used cASIC1a and tested the inhibitory activity of several Ma-1 mutants (Q5A, H6A, K8A, F27A, and R28A) at a single concentration of 500 nM, extending the peptide mutagenesis to include finger I (89). Using a single concentration of Ma-1, it is difficult to determine the true extent of loss in activity of each mutant peptide.…”
Section: Discussionmentioning
confidence: 99%
“…The binding site of mambalgins on ASICs has been studied by several groups using a combination of functional and structural techniques as well as docking studies. However, there is disagreement between these studies over the proposed binding orientation of mambalgins at ASICs (see Figure 6.11 for published models) (44,45,50,89,157). produced by rigid body fitting the cASIC1a desensitised crystal structure (PDB code 4FZ1) extracellular domain and mambalgin-1 crystal structure (PDB code 5DU1) into the cryo-EM density,…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation